2017
DOI: 10.1136/jnnp-2016-314495
|View full text |Cite
|
Sign up to set email alerts
|

The changing picture of amyotrophic lateral sclerosis: lessons from European registers

Abstract: Prospective population based Registers of amyotrophic lateral sclerosis (ALS) have operated in Europe for over two decades, and have provided important insights into our understanding of ALS.Here we review the benefits that population Registers have brought to the understanding of the incidence, prevalence, phenotype and genetics of ALS, and, outline the core operating principles that underlie these Registers and facilitate international collaboration. Going forward we offer lessons learned from our collective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 58 publications
2
66
2
Order By: Relevance
“…Engaging different professionals brings a diversity of approaches and expertise to the assessment, planning and management of care needs. A multidisciplinary team provides integrated and specialised care, which has been shown to result in better quality of life and possibly prolonged survival (Hardiman et al., ). A multidisciplinary approach also meets the needs of other domains.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging different professionals brings a diversity of approaches and expertise to the assessment, planning and management of care needs. A multidisciplinary team provides integrated and specialised care, which has been shown to result in better quality of life and possibly prolonged survival (Hardiman et al., ). A multidisciplinary approach also meets the needs of other domains.…”
Section: Discussionmentioning
confidence: 99%
“…While in the cohort from another single-center located in the southeast of China and the data from Hong Kong, it is only 29.67–33.6 months (Fong et al, 1996; Yang et al, 2011). It has been demonstrated that up to 70% of ALS patients die within 3 years of disease onset by the population-based registers from European countries (Hardiman et al, 2017). The inclusion criteria of each study were diverse.…”
Section: Epidemiologic Characteristics Of Chinese Als Patientsmentioning
confidence: 99%
“…Probably, this reflects the heterogeneity in the incidence of ALS in different countries. On the other hand, as indicated by Hardiman et al [31], the incidence of ALS is probably increasing due to a greater recognition of phenotypes, the emergence of centers specialized in MND, and the increase in the age range at risk for developing ALS.…”
Section: Discussionmentioning
confidence: 97%
“…To date there are no ALS genetic studies reported in Colombia, they would improve our discussion on the reported findings. In the present work, we used clear inclusion and exclusion criteria for cases selection, a good time for data collection and statistical analysis (5 years), and a defined capture methodology with multiple sources; as recommended by Hardiman et al [31] for studying behavior changes in MND. The reported high degree of agreement between raters increased data reliability, which is important for determining the diagnostic category [43].…”
Section: Discussionmentioning
confidence: 99%